RETRACTED ARTICLE "BEYOND “MY ENGLISH IS POOR”: UNPACKING THE SPEAKING CHALLENGES OF CHINESE EFL LEARNERS IN CHINA" - CHEA, PHALLA (Journal of Higher Education and Academic Advancement, 2024)
Retraction NoticeArticle Title: Beyond “My English is Poor”: Unpacking the Speaking Challenges of Chinese EFL Learners in ChinaJournal: Journal of Higher Education and Academic Advancement The article titled "Beyond “My English is Poor”: Unpacking the Speaking Challenges of Chinese EFL Learners in China" has been retracted at the request of the authors. The authors have formally requested the withdrawal of the article. The journal has reviewed the request and agreed to retract the article in accordance with the policy on retractions. The journal and the authors regret any inconvenience caused to the readers and stakeholders. Retraction Date: 19 December 2024 For any questions or further information, please contact the editorial office of the Journal of Higher Education and Academic Advancement.